Original paperSerum concentrations of metalloproteinase 2, metalloproteinase 9 and granzyme B in contact eczema patients - Wojciechowska, Milena; Żbikowska-Gotz, Magdalena; Czajkowski, Rafał; Bartuzi, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction : Contact eczema is a common skin condition with complex etiology, variable clinical presentation and lengthy therapy duration. The mechanism of contact eczema is complex, since it is affected by multiple inflammatory mediators. Aim: To assess concentrations of metalloproteinase 2 (MMP-2), metalloproteinase 9 (MMP-9) and granzyme B (GzmB) in patients with contact eczema. Material and methods : Seventy patients with contact eczema and 30 healthy persons as controls were included in the study. In all subjects, MMP-2, MMP-9 and GzmB were determined using ELISA immunoassay. In study group patients, concentrations were assayed in periods of disease exacerbation and remission. Obtained results were analyzed statistically. Results: Mean MMP-2 and GzmB concentrations were found to be significantly higher in the study group than in the control group. Mean MMP-2, MMP-9 and GzmB levels were also statistically significantly higher during skin lesion relapse compared to contact eczema remission periods. Conclusions : The presented paper demonstrates that MMP-2, MMP-9 and GzmB are good markers of contact eczema exacerbations.